Building A Generation of Reliable Entrepreneurs Through The Business Management Service Program at SMK Karya Nasional, Kuningan Regency, West Java - Susbiyantoro; Ferryal Abadi; Rahayu Tri Utami; Yoeliastuti; Eriene Iranie Nizarlie (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This Community Service activity was conducted to address the need for enhancing entrepreneurial skills among vocational school students, particularly at SMK Karya Nasional in Kuningan Regency, West Java. Vocational school graduates often face challenges in entering the workforce or starting their own businesses due to limited practical knowledge and skills in business management and entrepreneurship. The primary aim of this activity was to empower students by providing comprehensive training in business management, including topics such as basic business concepts, product development, marketing strategies, and entrepreneurial skills. The method used involved interactive workshops, hands-on practice, and collaboration with local industries to ensure practical application of the knowledge gained. As a result, the students demonstrated improved understanding of business concepts and management techniques, as well as greater confidence in applying these skills. This training also fostered stronger school-industry relations, creating opportunities for collaboration and internships that align education with the demands of the job market. In conclusion, this program successfully equipped students with the foundational skills required to pursue careers in business or entrepreneurship. It is hoped that this initiative can serve as a model for similar programs in other vocational schools, ultimately contributing to the growth of local economies through the development of student-led small and medium enterprises (SMEs).